2013
DOI: 10.1016/j.juro.2013.05.056
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the Prostate with Gleason Score 9-10 on Core Biopsy: Correlation with Findings at Radical Prostatectomy and Prognosis

Abstract: In the highly select subset of patients who are good surgical candidates and have the appropriate combination of preoperative variables postoperative findings are sufficiently favorable to justify radical prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…Because the postoperative determination of a tumors Gleason grade is "better" than the preoperatively determined Gleason grade (subjected to sampling errors and consequently undergrading in more than one third of cases; ref. 25), another multivariate analysis was added. In scenario 4, the preoperative Gleason grade obtained on the original biopsy was combined with preoperative PSA, cT stage, and p62 expression.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Because the postoperative determination of a tumors Gleason grade is "better" than the preoperatively determined Gleason grade (subjected to sampling errors and consequently undergrading in more than one third of cases; ref. 25), another multivariate analysis was added. In scenario 4, the preoperative Gleason grade obtained on the original biopsy was combined with preoperative PSA, cT stage, and p62 expression.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…[1][2][3][4][5] Of particular significance is the accurate identification of high-grade Gleason pattern 5 (GP5), as it indicates the most aggressive and potentially lethal PCa. [6][7][8][9][10][11] The presence of GP5 in NBX essentially classifies the PCa into Gleason score 8 to 10, a group that has traditionally been defined in a high-grade category for patient management. Recent studies have further demonstrated prognostic value of stratifying Gleason score 8 from 9 to 10 PCa.…”
mentioning
confidence: 99%
“…9 In our study, the patients with GS ≥ 8 had tendency to be in clinical T2c-T3b stage compared to be in clinical T1-2a stage. In GS ≥ 8 group, the percentage of the patients with PSA > 20 ng/ml and with PSA ≤ 10 ng/ml were 45% and 23%, respectively.…”
Section: Discussionmentioning
confidence: 47%